2012
DOI: 10.2989/16085906.2012.734978
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and coping strategies of orphaned children in Tanzania who are not adequately cared for by adults

Abstract: Orphaned children in poor rural communities sometimes have no adult who is able to care for them or else the adult caregiver is not able to provide adequate care. Tanzania remains one of the poorest countries in the world, and poverty frequently constrains foster care. Although HIV prevalence is declining, AIDS is still a major cause of orphaning. This article explores the challenges and coping strategies accompanying two possible life trajectories for orphaned children without adequate adult care: 1) that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In general, the growing OSC population is resulting in additional economic constraints and increasing caregiver burden felt by families in LMIC (Heymann, Earle, Rajaraman, Miller, & Bogen, 2007 ; Kidman & Thurman, 2014 ; Miller, Gruskin, Subramanian, Rajaraman, & Heymann, 2006 ). Studies have reported that economically constrained or inadequate orphan care in resource-poor areas can contribute to child- or sibling-headed households, increased child labor, reduced school attendance, and reduced educational attainment, all of which are associated with increased sexual health risk (Birdthistle et al, 2009 ; Case, Paxson, & Abledinger 2004 ; Cluver, Orkin, Boyes, Gardner, & Meinck, 2011 ; Dalen, Nakitende, & Musisi, 2009 ; Daniel & Mathias, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the growing OSC population is resulting in additional economic constraints and increasing caregiver burden felt by families in LMIC (Heymann, Earle, Rajaraman, Miller, & Bogen, 2007 ; Kidman & Thurman, 2014 ; Miller, Gruskin, Subramanian, Rajaraman, & Heymann, 2006 ). Studies have reported that economically constrained or inadequate orphan care in resource-poor areas can contribute to child- or sibling-headed households, increased child labor, reduced school attendance, and reduced educational attainment, all of which are associated with increased sexual health risk (Birdthistle et al, 2009 ; Case, Paxson, & Abledinger 2004 ; Cluver, Orkin, Boyes, Gardner, & Meinck, 2011 ; Dalen, Nakitende, & Musisi, 2009 ; Daniel & Mathias, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could be because of the fact that as these households had to struggle with the double burden of taking care of themselves and their siblings and with the trauma of losing their parents. Daniel & Mathias () have reported that living without adult support and care has led to children in these households facing abuse and exploitation. In this regard, Thurman et al () found that poverty, stigma and marginalization are also among the risks that child‐headed households in Rwanda struggle with on a daily basis, which could explain the high level of mental distress.…”
Section: Discussionmentioning
confidence: 99%
“…While the policies and programmes of governmental and non‐governmental aid organizations have focused mainly on community and family‐based care (Foster, ; UNICEF, ; Wakhweya et al ., ), they are often too resource‐constrained to provide adequate care for the growing number of orphans (Zimmerman, ). There are also many orphans falling outside the traditional methods of caring that received little attention from researchers (Daniel & Mathias, ).…”
Section: Introductionmentioning
confidence: 99%
“…Foster families primarily include the extended family, neighbors or other volunteers. There are also millions of orphans who live outside traditional community and family networks (Daniel & Mathias, ; Wakhweya, Dirks, & Yeboah, ). As a result, in the last decade, various types of living environments have evolved in Africa.…”
Section: The Buffering Role Of Social Support and The Psychosocial Wementioning
confidence: 99%